The first description of adult female of Borboropactus asper (O. P.-Cambridge, 1884) from Sri Lanka (Araneae: Thomisidae) - Marusik, Yuri M.; Omelko, Mikhail M.; Benjamin, Suresh P. (Zootaxa, 2013)
Regillus, a new genus of spiders with R. asper as its type species, was described by O.P.-Cambridge (1884) from Ceylon (now Sri Lanka) on the basis of a subadult female. The genus was placed in Cryptothelidae (now considered a subfamily of Zodariidae) due to its similarity with Cryptothele ceylonica O.P.-Cambridge, 1877. However, the new genus had a different eye arrangement, differently shaped maxillae and six spinnerets instead of two (O.P.-Cambridge 1884). Soon after, Simon (1895) recognized that this genus belonged to Thomisidae and synonymised his Borboropactus Simon, 1884 with Regillus. When it was found that Regillus was a junior homonym of the name used by Macgillivray in 1839 (for kinglets) Borboropactus was revalidated. Since the original description R. asper was redescribed only once, by Simon (1895), who illustrated its leg, chelicera and labium-maxilla complex (Simon 1895: figs 1094–1096). Wunderlich (2004) transferred Borboropactus to a new family Borboropactidae, which was rejected by Benjamin et al. (2008) and Benjamin (2011). However, the type species was never studied in any detail.